Gendered Differences in Household Engagement in Non-Farm Business Operations and Implications on Household Welfare: A Case of Rural and Urban Malawi - Wisdom Richard Mgomezulu; Javaid Ahmad Dar; Beston B. Maonga (Social Sciences)
Mainstreaming gender issues in a demographically divided setting remains a critical component in policy frameworks and project designs. The focus of this study revolves around male- and female-headed households’ engagement in business operations, with an extended effect on household welfare. This study uses Malawi’s Integrated Household Survey 5, and answers two research questions: Are there any determinants of household engagement in non-farm businesses in rural and urban areas of Malawi? And is there any impact of gender differentials in household engagements in non-farm business operations on household welfare in rural and urban areas of Malawi? This study notes that male-managed non-farm SMEs had better profits compared with their female counterparts, as described by the Probit and the Oaxaca two-fold decomposition models. Mediation analysis was later used to establish the impact of the gender differentials using profits as the mediating variable. In general, females were found to be better off, but the benefits were insignificant in reducing the general rural–urban gap. This study recommends the provision of support towards credit structures for rural households and women-headed households; improved financial and business literacy for increased engagement in business operations and reduced poverty; and support towards advocacy of gender inclusion in economic empowerment approaches.